Tax incentives and investment expansion: evidence from Zimbabwe’s tourism industry (2015)
This paper investigates the effects of tax incentives on investment growth in the tourism sector in less developed countries, using Zimbabwe as the case study. The study was prompted by the realisation that many less developed countries use tax incentives as means for luring investors into their countries yet there is a general lack of analysis on whether such tax incentives have any impact on social and capital growth. The study employed face-to-face and telephone interviews with key stakeholders in the tourism sector that were selected through stratified and random sampling methods. Questionnaires, distributed by hand, post and email were also used in situations where interviews were not feasible. Secondary data was used as a bedrock for detailed analysis. The paper established that most policy makers indeed use tax incentives to lure investors into the tourism industry but such policies are not followed by other supportive policies in other areas of the economy that help boost investment in the tourism sector. Other factors like corruption, transparency in government policies, length and cost of starting a business in the country, for instance, are other important factors that need to be taken into consideration. Among other recommendations there is a need for political stability, consistent and supportive policy, limited government interference in the industry, decentralization and opening up of more local and foreign tourism promotion centres, application of low tax rates across industries and the general creation of a favourable environment for the effectiveness of tax incentives.